(untitled) (The Peerian Journal, 2025)
This research explores the use of the Nearpod digital educational platform to enhance students’ learning effectiveness and foster their independent learning skills through interactive teaching methods. The study aimed to compare the learning outcomes of a control group, which used traditional teaching methods, with an experimental group that used the Nearpod platform for one academic quarter. The findings revealed a significant 13% improvement in the academic performance of the experimental group, highlighting the positive impact of digital technologies on student engagement and motivation. The study emphasizes the importance of incorporating interactive, gamified elements, and positive reinforcement into education, which can increase students’ participation, motivation, and overall learning outcomes.